Cille Pheadair : A Norse Farmstead and Pictish Burial Cairn in South Uist - Parker Pearson, Michael (Sheffield Environmental and Archaeological Research Campaign in the Hebrides Ser, 2018)
Cover -- Book Title -- Copyright -- Contents -- List of Figures -- List of Tables -- List of Contributors -- Acknowledgements -- 1. Cille Pheadair and the Norse period in South Uist: M. Parker Pearson -- 1. Previous research in Cille Pheadair township -- 2. The Viking Age and the Late Norse period in South Uist -- 3. The Viking Age and the Late Norse period in the Western Isles -- 4. The project's research design -- 5. The excavation 1996-1998 -- 6. This report -- 2. The Pictish burial cairn, cal AD 640-780: M. Parker Pearson -- 1. Introduction -- 2. The cairn -- 3. The burial -- 4. The small mammals in the burial -- 5. The human skeleton -- 6. Radiocarbon and stable isotope analysis -- 7. Combined lead, strontium and oxygen isotope analysis -- 8. Comparisons and discussion -- 3. Initial construction and occupation (phase 1), starting cal AD 945-1020: M. Parker Pearson and M. Brennand -- 1. Ploughing -- 2. The possible post-built structure -- 3. The sandbank and its stone revetment walls -- 4. The pits within the embanked enclosure -- 5. Soil micromorphology of windblown sand with ploughmarks (621) -- 6. Artefacts and other remains from the pits -- 7. Overview -- 4. The earliest deposits above the pits (phase 2), starting cal AD 945-1020: M. Parker Pearson and M. Brennand -- 1. Chronology and stratigraphy of the phase 2 features -- 2. Contexts within the sandbank enclosure -- 3. Contexts in the northern part of the sandbank enclosure and outside it -- 4. Outside the entranceway and east of the sandbank enclosure -- 5. The soil micromorphology of the levelling layer (600) -- 6. Artefacts and other remains from phase 2 -- 7. Overview -- 5. The first stone longhouse: House 700 (phase 3), constructed cal AD 1030-1095: M. Parker Pearson and M. Brennand -- 1. The house and its deposits -- 2. The spatial patterning of debris within the house floor.